2013
DOI: 10.1016/j.cell.2013.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Axon Branching Is Regulated by the LKB1-NUAK1 Kinase Pathway via Presynaptic Mitochondrial Capture

Abstract: SUMMARY The molecular mechanisms underlying the axon arborization of mammalian neurons are poorly understood but are critical for the establishment of functional neural circuits. We identified a pathway defined by two kinases, LKB1 and NUAK1, required for cortical axon branching in vivo. Conditional deletion of LKB1 after axon specification or knockdown of NUAK1 drastically reduced axon branching in vivo whereas their overexpression was sufficient to increase axon branching. The LKB1-NUAK1 pathway controls mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
361
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(381 citation statements)
references
References 55 publications
17
361
3
Order By: Relevance
“…3J-L). This is in good agreement with the requirement for mitochondria to provide energy throughout the large volume of the axon and to presynaptic active zones (Vos et al, 2010), and is also consistent with proposed roles for mitochondria in axon branch formation (Courchet et al, 2013). Fig.…”
Section: Restricted Pattern Of F-actin Marker Accumulation In Ms Axonssupporting
confidence: 75%
“…3J-L). This is in good agreement with the requirement for mitochondria to provide energy throughout the large volume of the axon and to presynaptic active zones (Vos et al, 2010), and is also consistent with proposed roles for mitochondria in axon branch formation (Courchet et al, 2013). Fig.…”
Section: Restricted Pattern Of F-actin Marker Accumulation In Ms Axonssupporting
confidence: 75%
“…and also able to arrest their transport along the axons [84]. Recently, for example, it has been demonstrated that the mitochondrial immobilization, via the LKB1-NUAK1 kinase pathway, is particularly important for axon branching at nascent presynaptic sites [85]. However, whether or not LKB1-NUAK1 interact with SYNTAPHILIN to promote axon branching has still to be investigated.…”
Section: Mitochondrial Transportmentioning
confidence: 99%
“…Organelle location can even affect a cell's shape. Neurons send out projections called axons to transmit impulses to other neurons, and axons tend to branch into two at spots where mitochondria, the cell's energy facility, have settled 3,4 . However, the effects of cellular layout can be difficult to unravel.…”
Section: Protein Partnersmentioning
confidence: 99%